2013
DOI: 10.1016/j.neuroimage.2013.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative patch-based super-resolution for diffusion-weighted images

Abstract: To cite this version:Pierrick Coupé, José V Manjón, Maxime Chamberland, Maxime Descoteaux, Bassem Hiba. Collaborative patch-based super-resolution for diffusion-weighted images.. NeuroImage, Elsevier, 2013 AbstractIn this paper, a new single image acquisition super-resolution method is proposed to increase image resolution of diffusion weighted (DW) images. Based on a nonlocal patch-based strategy, the proposed method uses a non diffusion image (b0) t o c o n s t r a i n t h e r e c o n s t r u c t i o n o f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 65 publications
(78 reference statements)
1
98
0
Order By: Relevance
“…Numerous machine-learning based methods have been proposed. For instance, [2,3] use example patches from HR images to super-resolve scalar MR and DW images respectively, with an explicitly defined generative model relating a HR patch to a LR patch and carefully crafted regularisation. Another generative approach is the sparse-representation methods [4,5], which construct a coupled library of HR and LR images from training data and solve the SR problem through projection onto it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous machine-learning based methods have been proposed. For instance, [2,3] use example patches from HR images to super-resolve scalar MR and DW images respectively, with an explicitly defined generative model relating a HR patch to a LR patch and carefully crafted regularisation. Another generative approach is the sparse-representation methods [4,5], which construct a coupled library of HR and LR images from training data and solve the SR problem through projection onto it.…”
Section: Introductionmentioning
confidence: 99%
“…We incorporate Bayesian inference into the framework and name the new method Bayesian IQT (BIQT). Although many SR methods [2][3][4][5] can be cast as maximum a posteriori (MAP) optimisation problems, the dimensionality or complexity of the posterior distribution make the computation of uncertainty very expensive. In contrast, the random forest implementation of the original IQT is amenable to uncertainty estimation thanks to the simple linear model at each leaf node, but the current approach computes maximum likelihood (ML) solution.…”
Section: Introductionmentioning
confidence: 99%
“…We then calculated Pearson's correlation between intra-subject SC and FC to quantify the consistency between the two connectivity estimates. Using this correlation measure, we compared the proposed super-resolution approach with trilinear and spline interpolation in addition to an alternative super-resolution method; collaborative and locally adaptive super-resolution (CLASR) [9]. To the best of our knowledge, CLASR is the only existing single image super-resolution method for dMRI which is independent of the diffusion model employed.…”
Section: Resultsmentioning
confidence: 99%
“…Even though this method eliminates the need for multiple acquisitions, it is only geared towards estimating diffusion tensors, and cannot be easily extended to higher order diffusion models such as orientation distribution functions (ODFs). To the best of our knowledge, the only previous work that tackled the problem of super-resolving dMRI data from a single acquisition independent of the diffusion model was by Coupé et al [9]. Specifically, the authors showed that super-resolving b=0 (non-diffusion-weighted) image using a locally adaptive patch-based strategy, and using this high-resolution b=0 image to drive the reconstruction of DW images outperforms upsampling of dMRI data using classical interpolation methods.…”
Section: Introductionmentioning
confidence: 99%
“…(24) is estimated as the restored value of square noisy image and 2 2  is a fixed signal independent bias which can be removed by subtracting it from each pixel in the magnitude squared image. (25) …”
Section: Multi-resolution Non-local Means Filtering For Mr Image Denomentioning
confidence: 99%